(untitled) (PERcursos Linguísticos, 2020)
Gender identity speech may present a revolutionary path when well discussed. However, such a path may not have a linear development, likely to present barriers and issues to be surpassed. The objective of this paper is to analyze the projected meanings on the narrative of a transgender person, as wells as to discuss the social repercussion that such a person faces in the academic context. The analysis will be performed in the selected portion of this speech, which composes the corpus of a greater 2018’s study involving the LGBTTQI+ scholar community. Methodologically, the Semiotics analysis guided the development of this study. Gender and transgender bibliography also added base to this paper, aiding in the analysis of the testimony. The results presented the presence of prejudice, intolerance, and stigmatization in and out of the academic context. At the same time, identity discovery, self-recognition, and respect aspects were unveiled by the analysis. Concluding, the analysis of the narrative also gives attention to matters such as segregation and exclusion of this social group.